Rancang Bangun E-Roster Berbasis Web Dengan Menerapkan Aspek Usability Testing - Mira Maisura; Dede Aminatus Saleha; Yusran Yusran (PTE FTK UIN Ar-Raniry, 2022)
One of the important things that support the implementation of an effective and efficient learning system is to manage data and related matters properly. E-roster, or the management of schedules and subjects in schools that are managed electronically, is one of the main options that is considered capable of improving data management problems. This research focuses on the design and development of the E-roster application to help the process of managing the learning list at school so that it continues to run well and optimally. This E-roster information system will provide convenience in compiling and managing learning lists, and providing comprehensive information to subject teachers and students. The research method applied is the RnD (Research and Development) method, with system development using the Waterfall method. For the analysis of the quality level of the web-based teaching and learning E-roster information system. It is based on testing five aspects of Usability Testing which consist of aspects of learnability, efficiency, memorability, errors, and satisfaction. The result showed that the test percentage of usability test is 78.6%, which indicates that the quality and ease of application of the E-roster is very good (SB).